2021
DOI: 10.1039/d0ra09742j
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional 4d transition metal doping in atomically thin lead

Abstract: To study the potential of plumbene as a dilute magnetic semiconductor, we computationally investigate the structural, electronic, and magnetic properties of 4d transition metal (TM) doped plumbene using density functional theory (DFT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Apart 3d metal dopants, the role of 4d transition metals for magnetization of TMDs like WSe 2 were investigated by Hashemi et al This new examination demonstrated the magnetization of the structure using Zr, Nb, Mo, and Tc dopants. However, any magnetic effect was not obtained in the structures doped by Y, Ru, Rh, and Pd elements 38 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Apart 3d metal dopants, the role of 4d transition metals for magnetization of TMDs like WSe 2 were investigated by Hashemi et al This new examination demonstrated the magnetization of the structure using Zr, Nb, Mo, and Tc dopants. However, any magnetic effect was not obtained in the structures doped by Y, Ru, Rh, and Pd elements 38 .…”
Section: Introductionmentioning
confidence: 88%
“…The regular methods to study the magnetic properties are based on the topology method, applying strain forces, vacuuming, and atomic vacancy defect generation. In addition, one of the most significant magnetization methods is doping the structure with transition elements of different periods of the periodic table 28 38 . Ataca et al 28 created the T and H-phase conditions on an extensive range of TMDs and investigated the magnetization conditions on the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Alexander et al studied the effects of doping MoS2 materials with 3d transition metals and resulted that Fe, Mn, and Co elements provide the maximum magnetic intensities in their doped structures 28 . By doping ZrS2 with transition elements and alkaline metals, Bayshan Yang et al demonstrated that Mn and Cr elements have the greatest magnetic influence, while Ni and Ti have no role in the system's magnetization 29 . In addition, Hashemi and his group performed a new examination on doping of the 2D structure of WSe2 using 4d elements and proved magnetization using Zr, Nb, Mo, and Tc.…”
Section: Introductionmentioning
confidence: 99%
“…Among the modification methods explored so far, 4d transition metal doping (Y, Zr, Nb, Mo, Ru, etc.) shows great potential in stabilizing the lattice framework of layered oxides. Recently, Yu et al captured the redox process of both oxygen and ruthenium during the first charge and discharge in Li 2 RuO 3 through advanced spectroscopy technology and discussed in detail the reversibility of anion redox, which provides information for the design of high-performance cathode materials using 4d transition metals to regulate anion redox . Wang et al employed DFT simulations to confirm that the substitution using Nb can promote charge compensation by transferring electrons to Mn and O and facilitate the diffusion of Li + ions, thus showing promise to improve the electrochemical performance of Li 2 MnO 3 .…”
Section: Introductionmentioning
confidence: 99%